Choroidal thickness of children's eyes with anisometropic and strabismic amblyopia - Aygit, Ebru Demet; Yilmaz, Ihsan; Ozkaya, Abdullah; Alkin, Zeynep; Gokyigit, Birsen; Yazici, Ahmet Taylan; Demirok, Ahmet (Journal of AAPOS, 2015)
To compare the choroidal thickness of children's eyes with amblyopia due to strabismus or anisometropia to the fellow eye and age-matched controls. Forty patients with anisometropic amblyopia, 40 patients with strabismic amblyopia, and 40 age-matched controls were included in this cross-sectional study. Choroidal thickness was measured via the enhanced-depth imaging technique of spectral domain optical coherence tomography in all patients and controls. Choroidal thickness was measured at subfoveal area and at 500 μm intervals to the nasal and temporal to the fovea up to 2000 μm. Measurements were compared between the three groups. The mean ages were 7.9 ± 2.6 years (range, 4-13 years) in the anisometropic group, 9.0 ± 3.7 (range 4-15 years) years in the strabismic group, and 8.4 ± 2.6 years (range 4-15 years) in the control group. The mean subfoveal choroidal thickness in the anisometropic group was 362 ± 82 μm in the amblyopic eyes and 301 ± 54 μm in the fellow eyes; in the strabismic group, 413 ± 82 μm in the amblyopic eyes and 316 ± 54 μm in the fellow eyes. The mean subfoveal choroidal thickness was 310 ± 78 μm in control eyes. The subfoveal choroids of both anisometropic and strabismic amblyopic eyes were significantly thicker than that of the fellow eyes of the corresponding groups and the control eyes (P < 0.05 for all). The subfoveal choroid of eyes with anisometropic and strabismic amblyopia is significantly thicker than that of the fellow eye and the age-matched controls.